INTERNATIONAL AND RUSSIAN EXPERIENCE OF INTERACTION BETWEEN AUDITING AND TAX ACCOUNTING - E. V. Golubtsova; K. S. Karavaeva (Вестник университета)
International and Russian experiences in the interaction of auditing and tax accounting have been studied. The differences between two accounting models, applying in various countries, have been analysed. The main characteristics of tax (continental) and proprietary (anglo-saxon) accounting models have been given. The analysis of two models of auditing and tax accounting has been carried out. The features of the Russian system of auditing and tax accounting have been considered. The main differences of auditing and tax accounting, using in the Russian Federation, have been analysed. The recommendations on improving the interaction of auditing and tax accounting, taking into account international practice in this area, have been given. It has been concluded about the influence of world experience on improving the Russian system of auditing and tax accounting.